Pengembangan Alat Praktikum Fisika Untuk Menunjukkan Pengaruh Cabai dan Tomat Pada Pembangkitan Tenaga Baterai Alternatif - Khasanah, Uswatun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This Research was conducted about the development of physics lab tools to show the effect of chilies and tomatoes on alternative battery power generation. This research aims to 1. find out whether tomatoes and chilies can be used as a source of electrical energy. 2. Find out what the mix optimum composition of tomatoes, chilies and water which can generate a maximum electrical energy. This research uses a proto-type of used batteries or batteries that are not used by removing manganese stone paste and replaced with a paste of chilies and tomatoes. This research used 2 samples consisting of a battery of mixed tomatoes and chilies without using additional water and a battery of mixed tomatoes and chilies using additional water in the mixture. Each battery has its potential difference measured. The next experiment was to create a closed circuit of each battery and connected with the LED lights, then measured the resulting voltage and current was generate. From the data it can be concluded that 1. the potential difference in a battery mixed with tomatoes and chilies without adding water is the best, namely when the composition of chilies is 100% 2. the potential difference in batteries mixed with tomatoes and chilies with the addition of water is best when the composition of tomatoes is 20% and chilies are 80%. 3. The average running time for LED lights in a closed circuit of mixed tomatoes and chilies, both with and without water, is 2 – 4 hours.